Perkembangan Pemikiran Islam Kontemporer - Komaruddin Hidayat (Faculty of Ushuluddin Syarif Hidayatullah State Islamic University, Jakarta, 1999)
The study of contemporary Islamic thought explores the dynamic and evolving nature of Islamic intellectualism in the modern world. This field examines how Muslim scholars and thinkers address current issues, reinterpret classical texts, and interact with global trends and ideologies. Key areas of focus include the engagement with modern science and technology, the challenges of globalization, the pursuit of social justice, and the reinterpretation of Sharia in contemporary contexts. By analyzing the contributions of various contemporary Muslim thinkers, this study aims to understand the ongoing development and transformation of Islamic thought and its implications for the Muslim world and beyond.